CLONING AND CHARACTERISATION OF ACC OXIDASE GENE FROM MAS (AA) BANANA - Kunasekaran, Wijenthiran; Boyce, Amru Nasrulhaq; Somasundram, Chandran (Malaysian Journal of Science, 2011)
Considerable experimental attention has been given to amplify Mas (AA) ACC oxidase gene from Mas (AA) banana (Genbank accession number: EU106081). ACO gene from Mas (AA) has been compared with other homologous gene by using bioinformatics tools to study the characteristics of the gene such as evolutionary history, binding sites, predicted 3D structure and consensus region of the homologous proteins. The finding shows that Mas ACO is member of iron/ascorbate-dependent oxidase superfamily which requires ascorbate and iron for full activity so that it will meet the all the criteria requires as it is expressed in vivo to produce ethylene. Abstrak Kaedah tertentu telah digunakan untuk mengamplifikasikan gen Mas (AA) ACC oksidase dari pisang Mas (AA) (Nombor Akses Genbank: EU106081). Gen ACC oksidase adalah dari Mas (AA) telah dibandingkan dengan sepuluh gen homologus yang lain dengan menggunakan peralatan bioinformatik untuk mengkaji ciri-ciri, sejarah evolusi, tapak pengikatan, ramalan struktur 3D dan konsensus protein homologi. Berdasarkan dari penemuan ini, didapati bahawa Mas ACO merupakan ahli keluarga oksidase yang bergantung kepada besi/askorbat untuk menjalankan akitiviti sepenuhnnya yang lengkap sepertimana ianya dihasilkan secara ’in vivo’ untuk menghasilkan etilena. (Keywords: ACC Oxidase (ACO), Ethylene, Mas (AA) banana, Musa acuminata, bioinformatics)